Electron driven scattering studies involving diborane. Issue 18 (January 2020) - Yadav, H; Prajapati, D; Vinodkumar, M; Vinodkumar, P C
Synopsis: In the present case we study the electron impact scattering cross sections on diborane ( B2 H6 ) for the energy range 0.1 eV to 5000 eV. The present study provides differential cross sections (DCS), momentum transfer cross sections (MTCS), ionization cross sections and total scattering cross sections (TCS). The experimental determinations of these cross sections are rather difficult dur to its complex structure and stability. These cross sections are important in many applied fields.